Selection in blood cells from female carriers of the fragile X syndrome: inverse correlation between age and proportion of active X chromosomes carrying the full mutation. Issue 12 (December 1991) - Rousseau, F; Heitz, D; Oberlé, I; Mandel, J L
Abstract : We have studied the patterns of mutation and X inactivation in female carriers of a fragile X mutation, to try to correlate them with various phenotypic features. We used a simple assay, which shows simultaneously the size of the mutation, its methylation status, and DNA fragments that represent the normal active and inactive X chromosomes. We have observed an age dependent process, whereby the 'full' fragile X mutation is found preferentially on the inactive X in leucocytes in adult females, but not in younger ones. This phenomenon was not observed in female carriers of a 'premutation', who have little phenotypic expression. Preliminary data suggest that young females who show preferential presence of a full mutation on the active X in leucocytes may be at increased risk for mental retardation. We have also obtained preliminary evidence for an age dependent decrease in the somatic heterogeneity of full mutations, possibly owing to selection for smaller mutated fragments. If confirmed, the latter phenomenon might account for the known decrease with age of the expression of the fragile site. Our observations suggest that a gene whose expression is affected by the presence of a full mutation (possibly the FMR-1 gene) has a cell autonomous function in leucocytes, leading to a slowly progressive selection for cells where the mutation is on the inactive X chromosome.